Subcellular Localization of GIGANTEA Regulates the Timing of Leaf Senescence and Flowering in Arabidopsis - Kim, Hyunmin; Park, Su Jin; Kim, Yumi; Nam, Hong Gil (Frontiers in Plant Science, 2020)
Plants undergo several important developmental transitions including flowering and senescence during their life cycle. Timing these transitions according to the environmental conditions increases plant fitness and productivity. The circadian clock senses various environmental cycles, including photoperiod, and synchronizes plant physiological processes to maximize plant fitness. Here, we propose that the cellular localization of GIGANTEA (GI), a key clock component, regulates leaf senescence and flowering in Arabidopsis thaliana. We show that GI, which connects the circadian clock with photoperiod-regulated flowering, induces leaf senescence depending on its subcellular localization. Overexpression of GI in the gi mutant rescued its delayed senescence phenotype but only when the GI protein was targeted to the nucleus, not when it was targeted to the cytosol. In the nucleus, EARLY FLOWERING 4 (ELF4) inhibited the binding of GI to ORESARA 1 (ORE1) promoter to regulate leaf senescence. GI also positively regulated the day-peak of ORE1 expression. These results indicate that like flowering, leaf senescence is also controlled by the location of GI in the cell. Taken together, our results suggest that ELF4 and GI act together to control flowering and senescence in Arabidopsis.